3-Hydroxybutyrate helps crayfish resistant to Vibrio parahaemolyticus infection in versatile ways. Issue 132 (January 2023) - Duan, Hu; Zuo, Jiajun; Pan, Namin; Cui, Xueping; Guo, Jianlin; Sui, Liying
Abstract: The bacterial storage compound poly-β-hydroxybutyrate (PHB) is a potential bio-control agent in aquaculture. It has been reported that PHB benefit to the survival and growth, and improve their immunity of aquatic animals. However, the cellular and molecular regulation mechanisms of PHB in immunity process remain unclear. This study investigated the immune mechanism of hemocytes regulated by Halomonas -PHB (PHB-HM) and PHB monomer 3-HB. Red claw crayfish Cherax quadricarinatus was used as the experimental animal in cytological study. Fluorescence microscopy and flow cytometry (FCM) analysis indicated that PHB-HM labeled with fluorescein isothiocyanate (FITC) could be engulfed by granulocytes (Gs) and semi-granulocytes (SGs) upon in vitro incubation. Transmission electron microscopy (TEM) further showed the ongoing degradation of PHB granules inside Gs and SGs after the injection of PHB-HM into crayfish sinus, but phagocytosis of PHB-HM by hyalinocyte (H) was not observed. Therefore, Gs and SGs are considered the main effector cells of cellular immunity induced by PHB-HM, and SGs likely played a particular important role in this process. To study the biosafety and molecular mechanism of PHB monomer 3-HB, hemocyte viability and expression of the related genes were determined after being exposed to 0–1 mg/mL of 3-HB, and Vibrio parahaemolyticus (VP) was used as the pathogenic bacterium. The results confirmed that 3-HB had no toxic effect on hemocytes by means of cell viability assay, and supplementation with 1 mg/mL of 3-HB suppressed the growth rate of VP in TSB medium. Moreover, injection of 3-HB into the blood sinus of crayfish remarkably improved the phagocytic rate of Gs and SGs on VP. Furthermore, transcriptome assay was designed to illuminate the molecular mechanism of 3-HB regulation using red swamp crayfish Procambarus clarkii as experimental animals. RNA-seq analysis and qRT-PCR verification revealed that the microtubule and cytoskeleton-related genes were high expressed 3 h after 3-HB injection, indicating both genes might involve in building up the innate immunity. In summary, bacterial storage PHB could be phagocytosed by main effector blood cells and likely to be degraded within the cells. 3-HB helped the crayfish resistant to pathogens through improving phagocytosis, suppressing the growth of pathogenic bacteria, and increasing the expression of microtubule-related genes. The findings in this work provide cytological and molecular evidence which will facilitate the application of PHB and 3-HB as immune-control agents in farming of aquatic animals. Highlights: Granular cells (Gs) and Semi-Granular cells (SGs) were considered the main effector cells of cellular immunity induced by PHB-HM. PHB granules were degraded in hemocytes of crayfish. 3-HB remarkably improved the phagocytic rate of Gs and SGs on Vibrio parahaemolyticus. 3-HB induced the microtubule and cytoskeleton-related genes which might involve in building up the innate immunity.